The learning motivations of the underprivileged students - Horváth, Ádám (Studia Mundi – Economica, 2015)
This survey was researching the social features of the underprivileged students at two primary school and at two vocational school in Northern Hungary and in the Northern Great Plain by the help of the students and directors.In the selected schools are learning in surpassingly high rate the underprivileged, and multiply underprivileged students, therefore I could got real information about the pedagogical specialities of the students, from the points of view of the students and the directors.